Development of modified neurotoxicity testing systems based on zebrafish [Danio rerio (Hamilton 1822)] behavioral response - Mohd Sata, Nurul Syafida Asma' (2018)
Behavior is one of the parameters used in the chemical testing for neurotoxicity research, due to its direct relationship to the nervous system functionalities. Currently, there are many behavioral systems that are available in the market but, the price to set them up in a small-scale laboratory can be costly. Thus, the aims of this study include to improve and upgrade a highthroughput anxiety related behavioral testing system for zebrafish (Danio rerio) larvae, to set up and validate a locomotor behavioral testing system for zebrafish larvae and lastly, to set up and validate a low cost behavioral testing system for adult zebrafish. The methodologies involved the construction of all structures for the behavioral setup, followed by the testing and validation of the systems. The automated high throughput assessment was used to test the sensorimotor responses of different caffeine concentrations (25, 50, 75 and 100 mg/L) towards the anxiety-like behavior in 6 days post fertilization (dpf) larvae. The results showed that the higher concentration of caffeine had an apparent anxiogenic effects on the larvae’s responses and reduced locomotor activity. The LSRtrack and LSRanalyze program was used to study the differences in the locomotor activity for 6 dpf zebrafish larvae, between the control larvae and 100 mg/L of caffeine treated larvae. Analysis showed that 100 mg/L treated larvae had a significantly lower locomotor activities than control larvae. The adult system, DanioJ was used for the short term habituation tests for adult zebrafish, and Javanese medaka (Oryzias javanicus). The results showed that the behavior responses in both of the fish controvert to each other, over time. The use of these behavioral testing systems allowed us to reduce the cost needed to establish a proper behavior testing in the laboratory, without neglecting the accuracy of results obtained, since all of the results obtained were in sync with past studies.